Ayquatiá da Yapepó - Estudo dos Materiais Utilizados na Cerâmica: Pintada Tupiguarani de Minas Gerais - Camila Pereira Jácome (2006)
The focus of the present work is the study of the materials used on tupiguaranipainted pottery in the state of Minas Gerais. The observed ceramics were collectedfrom the archeological sites of Florestal II (Itueta-MG), Vassoural (Andrelândia-MG)and the Aníbal Mattos collection, all of then part of the Natural History Museumcollection of works. The pieces were analyzed using Polarized Light Microscope(PRN), Infrared Spectroscopy, RAMAN, X-Rays Diffraction, and Neutron ActivationAnalysis performed by technicians from LACICOR and CDTN. By applying thesetechniques, we intended to analyze the constitution of inks and other ornamentalmaterials as well as find a sequence of layers in the images structure throughrecreating crossections, and to find out the mineralogical and chemical constitutionwithin samples of different types of clays and ceramics.